Zoonotic Visceral Leishmaniasis: New Insights on Innate Immune Response by Blood Macrophages and Liver Kupffer Cells to Leishmania infantum Parasites - Armanda Viana Rodrigues; Ana Valério-Bolas; Graça Alexandre-Pires; Maria Aires Pereira; Telmo Nunes; Dário Ligeiro; Isabel Pereira da Fonseca; Gabriela Santos-Gomes (Biology, 2022)
L. infantum is the aetiological agent of zoonotic visceral leishmaniasis (ZVL), a disease that affects humans and dogs. Leishmania parasites are well adapted to aggressive conditions inside the phagolysosome and can control the immune activation of macrophages (MØs). Although MØs are highly active phagocytic cells with the capacity to destroy pathogens, they additionally comprise the host cells for Leishmania infection, replication, and stable establishment in the mammal host. The present study compares, for the first time, the innate immune response to L. infantum infection of two different macrophage lineages: the blood macrophages and the liver macrophages (Kupffer cells, KC). Our findings showed that L. infantum takes advantage of the natural predisposition of blood-MØs to phagocyte pathogens. However, parasites rapidly subvert the mechanisms of MØs immune activation. On the other hand, KCs, which are primed for immune tolerance, are not extensively activated and can overcome the dormancy induced by the parasite, exhibiting a selection of immune mechanisms, such as extracellular trap formation. Altogether, KCs reveal a different pattern of response in contrast with blood-MØs when confronting L. infantum parasites. In addition, KCs response appears to be more efficient in managing parasite infection, thus contributing to the ability of the liver to naturally restrain Leishmania dissemination.